Determination of superplastic properties from the results of technological experiments. (October 2017) - Kruglov, A.A.; Ganieva, V.R.; Enikeev, F.U.
Abstract: The problem to determine experimentally the values of material parameters for two material models of superplastic flow, σ=Kξ m and σ = K ′ξ m ′ ε n, from the results of technological trials is considered. With this in view, a special computational procedure is developed to minimize the deviation of the theoretically predicted forming times from experimental data recorded during constant pressure forming trials of a sheet into a circular die. As compared with similar procedures known in the literature the methods suggested enable one to obtain a unique set of material parameters by using the whole set of available experimental data. The validity of the procedures suggested is confirmed by means of comparing the results obtained with corresponding finite element solutions. The accuracy of modeling of the experimentally measured values of the forming time is found to be better than 5% for all cases considered.